Deutsche Wirtschaft. Życie gospodarcze w Sieradzu w czasie okupacji 1939–1945 - Lesiakowski, Krzysztof (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
In Nazi propaganda pharse „German economy” (Deutsche Wirtschaft) was treated as a symbol of German’s superiority over its eastern neighbour. The analysis of economic life in Sieradz, which in 1939 was included into Germany, allows to evaluate whether in this propagandist thesis were elements of truth? In practice, Nazi occupation in sphere of economic life meant the plunder of property belonging to Polish and Jewish occupants. In German’s and German migrants’ hands hit all of biggest production companies (mills, dairy, brewery, disstilery, factory of agricultural machines, factory of asphalt roofing), storehouses of materials, majority of shops and gastronomic placements. The production was subordinated to military purposes, which meant extreme exploitation of machines and equipments, liquidation of some works and total rationing of food and industrial products. In time of occupation, in Sieradz none of new firms came into being, except of building companies, which began working because of constructing German military training ground, in neighbourhood of this city. This example proves that the pharse “German economy” didn’t mean anything different than propagandist slogan.